2015
DOI: 10.4048/jbc.2015.18.4.303
|View full text |Cite
|
Sign up to set email alerts
|

New Findings on Breast Cancer Stem Cells: A Review

Abstract: Since the introduction of the "cancer stem cell" theory, significant developments have been made in the understanding of cancer and the heterogenic structure of tumors. In 2003, with the isolation of cancer stem cells from the first solid tumor, breast cancer, and recognition of the tumorigenicity of these cells, this theory suggested that the main reason for therapy failure might be the presence of cancer stem cells. This review article describes breast cancer stem cell origin, the related cellular and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(71 citation statements)
references
References 131 publications
0
71
0
Order By: Relevance
“…To further investigate the effect of vitamin D compounds on cancer stem-like cells in TNBC, we analyzed SUM159 mammospheres treated with vitamin D compounds for expression of pluripotency and stem cell genes which have been shown to be important in breast cancer progression (19). The pluripotency marker, OCT4, was greatly reduced by treatment with 100 nM 1α,25(OH) 2 D 3 (29%, p <0.01) and 10 nM BXL0124 (39%, p <0.05) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate the effect of vitamin D compounds on cancer stem-like cells in TNBC, we analyzed SUM159 mammospheres treated with vitamin D compounds for expression of pluripotency and stem cell genes which have been shown to be important in breast cancer progression (19). The pluripotency marker, OCT4, was greatly reduced by treatment with 100 nM 1α,25(OH) 2 D 3 (29%, p <0.01) and 10 nM BXL0124 (39%, p <0.05) (Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…(A) qPCR analysis was performed on primary mammospheres harvested after five days of growth to assess the gene expression of Oct4, CD44, LAMA5 and NF-κB. Average Ct values are shown in parenthesis for OCT4 (22), CD44 (19), LAMA5 (22), and NF-κB (23). The experiments were repeated three times.…”
Section: Figurementioning
confidence: 99%
“…For example, recent work revealed that low CD24 surface expression leads to only a ~50% decrease in metastatic cancer burden while shRNA mediated silencing of CD24 results in a 90% decrease (9). In addition, ourselves (9) and others (17) have shown that cancer cells with little to no surface CD24 (surCD24-) retain significant tumorigenic properties. Together, these data suggest that CD24 exists in additional cellular locations and has significant biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, overexpression of GRP78 in both breast cancer cell lines caused an induction of the TIC subpopulation (i.e. CD24 -/CD44 + cells) [26] ( Figures 3A and 3B). Overexpressing GRP78 also induced the expression of aldehyde dehydrogenase 1 (ALDH1A), a marker associated with stemness and cancer [27] (Supplementary Figure S4).…”
Section: Resultsmentioning
confidence: 96%
“…Although sGRP78 shared similar functions on stem cells and cancer cells, whether or not sGRP78 expression was marking and/or affecting a stem-like subpopulation within breast cancer remained unclear. To begin to analyze the potential role of sGRP78 expression in stemness in cancer, we performed experiments with the breast cancer cell lines MCF7 (luminal A subtype [25]) and MDA-MB-231 (basal subtype [25]) that contain low or high levels of previously defined CD24 -/CD44 + tumor initiating cells (TICs) respectively, a cell population with breast cancer cells shown to be able to generate tumors with much higher efficiency in in vivo xenograft transplantation assays [26]. Interestingly, overexpression of GRP78 in both breast cancer cell lines caused an induction of the TIC subpopulation (i.e.…”
Section: Resultsmentioning
confidence: 99%